ESG on Stability and Bank Performance: The Moderating Role of Diversity and Inclusion in OIC Countries - Muhammad Irsyad; Fauziah Chairiyati (Universitas Islam Internasional Indonesia, 2025)
This study analyses the impact of environmental, social and governance (ESG) performance on the stability and performance of Islamic banks, considering the moderating role of diversity and inclusion. Using panel data from 60 Islamic banks in 11 Organisation of Islamic Cooperation (OIC) countries during the period 2014-2023, the research finds that ESG performance positively affects the stability and performance of Islamic banks, confirming the role of sustainability in enhancing the financial resilience of the Islamic banking sector. However, this study also finds that diversity and inclusion weakens the positive impact of ESG performance on the stability and performance of Islamic banks. Additional analysis shows that these results are consistent only in the environmental and social pillars. These findings highlight the importance of managing diversity and inclusion to enhance ESG implementation in Islamic banks. Poorly managed diversity and inclusion efforts may weaken ESG effectiveness, hindering performance and stability. For stakeholders, including investors and regulators, fostering inclusion is essential to support sustainability and long-term stability.